2020
DOI: 10.1016/j.cjtee.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Using modified Delphi method to propose and validate the components of a child injury surveillance system for Iran

Abstract: Purpose Child injuries are a public health concern globally. Injury surveillance systems (ISSs) have beneficial impact on child injury prevention. There is a need for evidence-based consensus on frameworks to establish child ISSs. This research aims to investigate the key components of a child ISS for Iran and to propose a framework for implementation. Methods Data were gathered through interview with experts using unstructured questions from January 2017 to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The modified Delphi technique (Azadi, et al , 2020) was adopted in this step. For this purpose, five tourism experts participated in the Delphi method to specify the factors.…”
Section: Finding and Resultsmentioning
confidence: 99%
“…The modified Delphi technique (Azadi, et al , 2020) was adopted in this step. For this purpose, five tourism experts participated in the Delphi method to specify the factors.…”
Section: Finding and Resultsmentioning
confidence: 99%
“…18 The MDS development process described here could prove beneficial for standardising data collection, managing patients’ care and improving quality of care. Different studies have pointed out the importance of standard clinical documentation 19 including RA patients. 18 , 20 22 Bajraktari studied 951 patients with RA and found a significant relationship between demographic characteristics data such as gender, nationality, marital status, education level, and occupation and prevalence rate of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with other recommendations. 19 , 29 The several instruments for capturing data related to for instance, laboratory tests or drugs were not discussed in the focus groups and the Delphi process as the main aim of this study was first to identify required data items. However, as the standardisation of the clinical data which has to be collected by the MDS is of high importance, in further studies the best guideline and recommendations have to be identified for necessary clinical data elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future enhanced tourniquets present new possibilities for automated capabilities that are more intuitive, more instructive, and promote proper placement and use. To determine the capabilities needed for these smart tourniquets, we employed a modified Delphi survey methodology to establish a consensus, an agreement among a set of tourniquet subject matter expert (SME) panelists, to define what these capabilities should be 17–20 . The Delphi Method is a framework for implementing qualitative research studies to determine consensus, or lack thereof, among a wide breadth of SMEs 19,21 .…”
mentioning
confidence: 99%